Strategi Penanaman Nilai Moderasi Beragama Kepada Siswa Di Lingkungan Pesantren - Habibi, Ibnu (Proceedings of Annual Conference for Muslim Scholars, 2023)
This research aims to describe the strategies used by Islamic boarding school managers or educators in instilling the values of religious moderation in students in the Islamic boarding school environment, the obstacles in instilling the values of religious moderation, and the efforts made by Islamic boarding schools to overcome these obstacles. The objects of this research are SMP MBS Al-Amin Bojonegoro.This research uses a descriptive qualitative approach using interview, observation and documentation methods. The data source is primary data sourced from kiai, coaches, teachers and students. Meanwhile, secondary data is taken from documents related to the research.The results of this research are 1) Instilling the values of religious moderation is implemented through strategies, namely; first, the madrassy/formal class method, in the form of classroom education that follows the national education system. Second, the halaqah method. The halaqah recitation is delivered by the kiai/ustadz after every sunset and dawn at the mosque by studying the yellow book. Third, extracurricular arts activities which will be presented at the end of the year. Fourth, hidden curriculum, namely everything that influences students related to positive behavior. 2) Obstacles in instilling the values of religious moderation among others; limited time, low student enthusiasm in activities, and students' lack of understanding of the importance of religious moderation. 3) Efforts made by Islamic boarding schools to overcome obstacles include specifically scheduling religious moderation lessons, requiring the participation of students in activities, and presenting applicable activities about the importance of the values of religious moderation